Sabbatai Zwi - ein Bruder des Messias Jesus?: Anmerkungen und Fragen zu einer schwierigen Verwandtschaft - Petzel, Paul (Zeitschrift für katholische Theologie, 2005)
The essay formulates theological consequences from certain similarities between the 17th century messianic figure Sabbatai Zvi and Jesus Christ. When Buber speaks of Zvi as the borther of Jesus, christian theology cannot but take this up in order to formulate a more authentic christology.